Differences in myocardial strain between pectus excavatum patients and healthy subjects assessed by cardiac MRI: a pilot study. - Lollert, André; Emrich, Tilman; Eichstädt, Jakob; Kampmann, Christoph; Abu-Tair, Tariq; Turial, Salmai; Düber, Christoph; Kreitner, Karl-Friedrich; Staatz, Gundula (European Radiology, 2018)
Objectives: To evaluate differences in myocardial strain between pectus excavatum (PE) patients and healthy subjects (HS) assessed by cardiac MRI using the feature-tracking algorithm.Methods: Cardiac MRI was performed in 14 PE patients and 14 HS (9:5 male to female in each group; age 11-30 years) using a 3T scanner. Post-examination analysis included manual biventricular contouring with volumetry and ejection fraction measurement by two independent radiologists. Dedicated software was used for automated strain assessment.Results: In five of the PE patients, the right ventricular ejection fraction was slightly impaired (40-44 %). PE patients had a significantly higher left ventricular longitudinal strain (P=0.004), mid (P=0.035) and apical (P=0.001) circumferential strain as well as apical circumferential strain rate (P=0.001), mid right ventricular circumferential strain (P=0.008) and strain rate (P=0.035), and apical right ventricular circumferential strain (P=0.012) and strain rate (P=0.044) than HS. The right ventricular longitudinal strain and strain rate did not differ significantly between PE patients and HS.Conclusions: Myocardial strain differs significantly between PE patients and HS. Higher myocardial strain in the mid and apical ventricles of PE patients indicates a compensation mechanism to enhance ventricular output against basal sternal compression.Key Points: • The right ventricle is frequently affected by the pectus excavatum deformity. • Cardiac MRI revealed differences in myocardial strain in pectus excavatum patients. • Pectus excavatum patients exhibited higher strain in the mid/apical ventricles. • A compensation mechanism to enhance ventricular output against sternal compression is possible.